2016
DOI: 10.1167/iovs.16-19785
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Inherited Retinal Diseases in Indigenous African Populations by Whole-Exome Sequencing

Abstract: PurposeA majority of genes associated with inherited retinal diseases (IRDs) have been identified in patients of European origin. Indigenous African populations exhibit rich genomic diversity, and evaluation of reported genetic mutations has yielded low returns so far. Our goal was to perform whole-exome sequencing (WES) to examine variants in known IRD genes in underrepresented African cohorts.MethodsWhole-exome sequencing was performed on 56 samples from 16 families with diverse IRD phenotypes that had remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Exome sequencing of a panel of 217 known IRD-associated genes was negative 18 , but analysis of ERDC candidate genes (http://www.erdc.info/candidateirdgenes) revealed biallelic variants in IDH3A which segregated with the disease phenotype (Figure 1). Screening of these variants in a set of 16 indigenous African families (n=56 individuals) with IRDs was negative.…”
Section: Resultsmentioning
confidence: 99%
“…Exome sequencing of a panel of 217 known IRD-associated genes was negative 18 , but analysis of ERDC candidate genes (http://www.erdc.info/candidateirdgenes) revealed biallelic variants in IDH3A which segregated with the disease phenotype (Figure 1). Screening of these variants in a set of 16 indigenous African families (n=56 individuals) with IRDs was negative.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the multitude of loci associated with IRDs (almost 300 loci, ), molecular diagnostics often relies on targeted enrichment and high-throughput sequencing, either whole-exome (WES) [ 3 , 4 , 5 , 6 ] or gene panels [ 5 , 6 , 7 , 8 , 9 , 10 ]. Studies have reported that diagnostic yield when using these standard methods (WES/gene panels) is typically between 50% and 76%, depending, amongst other factors, on the specific clinical subtype being investigated [ 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…the variant has been found in 2 unrelated probands. 2 size of the deletion: 3999-4033 bp (NC_000001.10:g.(94507656_94507700)_ (94511700_94511710)del) 3. size of the deletion: 70,036 bp (NC_000009.11:g.2716981_2787016del).…”
mentioning
confidence: 99%
“…In an effort to elucidate the genetic landscape of IRD among the indigenous African populations of South Africa (SA), WES was previously performed in a cohort of 16 families, and a molecular diagnosis obtained for approximately 40% through an analysis of all reported IRD genes at that time ( n = 285) [ 25 ]. Leveraging the vast genomic diversity of indigenous Africans in SA [ 26 , 27 , 28 , 29 , 30 , 31 ] yielded several novel mutations [ 25 ] and assisted the identification of a novel IRD gene [ 32 ]. Subsequently, the WES data from five unresolved families with an absence of male-to-male disease transmission were re-interrogated, confirming that ORF15 had been insufficiently captured.…”
Section: Introductionmentioning
confidence: 99%